Om Polen i svensk dagspress - Żmuda-Trzebiatowska, Magdalena (Folia Scandinavica Posnaniensia, 2007)
The following article is a part of research on the image of Poland in Sweden and Sweden in Poland done for the author’s PhD dissertation. The analysis of newspaper articles published in Swedish newspapers since 1987 till 1997 showed the most popular issues on Poland. They are: pollution, the situation of Polish Jews and the position of the Catholic church in Poland, Polish-German and Polish-Russian bilateral relations. The issues are described completely in the articles, however, they become generalised and stereotyped in overseas reports.